Handbook of development and relief - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The Oxfam handbook of development and relief 1995 by Deborah Eade and Suzanne Williams Volume One ISBN 0 85598 3078 Volume Two ISBN 0 85598 308 6 Volume Three ISBN 0 85598 309 4 Complete Set (in rigid slipcase) ISBN 0 85598274 8